Sistem Operasional Akad Ijarah Pada Kinerja Tukang Bangunan Menurut Ekonomi Islam di Desa Kertagena Tengah Kabupaten Pamekasan - Fakhruzy, Agung (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
The house-building business in the Central Kertagena Village is one of the businesses that are of concern to the community by using a timing system with